Determinants of Loan Repayment of Micro and Small Enterprises in Jimma town, Ethiopia (Global Journal of Management and Business Research, 2018)
The main objective of this study was to examine the determinants of loan repayment of Micro and Small Enterprises (MSEs) in Jimma town, Ethiopia. This study examined the effect of Individual characteristics, loan characteristics and firm characteristics on loan repayment of micro and small enterprises in Jimma town only. The study used descriptive research design. Primary data was collected through self administered questionnaire and it was collected from random samples of 341 Micro and Small Enterprises (MSEs) by stratifying into Five group. Once the relevant data was gathered, the collected data was analyzed through descriptive and econometric model known as binary logistic regression model was used in order to examine determinants that impeding Micro and small enterprise's loan repayment by distinguishing characteristics of MSEs. The descriptive result of analyzed data revealed that individual characteristics, loan characteristics and firm characteristics influenced loan repayment of enterprises in the study area. In addition, the result of binary logistic regression model indicated that Sex of respondents and Experience positively and significantly affect loan repayment. The inconvenience of loan payback period, Lack of financial skill and planning negatively and significantly affected loan repayment of enterprises. Lack of Marketing Skills, Follow up and supervision positively and significantly influenced loan repayment of micro and small enterprises.
Keywords: micro and small enterprises; lack of loan repayment; individual characteristics; loan characteristics; firm characteristics; jimma town